Understanding Fear of Breast Cancer Among Ghanaian Women via the Champion Breast Cancer Fear Scale - Enoch Teye-Kwadjo (Breast Cancer: Basic and Clinical Research)
Background: Screening for breast cancer via mammography is underutilised in Ghana, with fear of the disease influencing women’s participation. However, little is known about the role fear of breast cancer plays in screening decisions, partly due to the lack of a Ghana-specific measure to assess this fear. There is a need for a valid and reliable measure to assess breast cancer-related fear among Ghanaian women. Objectives: To evaluate the construct validity and internal consistency reliability of the Champion Breast Cancer Fear Scale among Ghanaian women. Design: Cross-sectional research design. Methods: The participants were women (aged 18-78 years) recruited in the general population through convenience sampling. The total sample was randomly split into 2 equivalent subsamples to perform the construct validity analysis via exploratory factor analysis (n = 428) and confirmatory factor analysis (n = 427), along with internal consistency reliability testing using McDonald omega (ω) and Cronbach alpha (α). Results: The original one-factor structure of the Champion Breast Cancer Fear Scale was supported by both exploratory factor analysis and confirmatory factor analysis in the present study. Omega and alpha coefficients for the total sample (ω = .877; α = .876), subsample 1 (ω = .877; α = .875), and subsample 2 (ω = .879; α = .877), were found to be good. Overall, the confirmatory factor analysis found sound validity evidence, χ 2 (19) = 62.84, P  < .001, comparative fit index = .971, root mean square error of approximation = .074, 90% confidence interval = [.05, .09], standardised root mean square residual = .031, for the use of the Champion Breast Cancer Fear Scale for assessing fear of breast cancer among Ghanaian women in the general population. Other results revealed that most of the participants reported a high fear of breast cancer, whereas a substantial number reported a moderate fear of breast cancer. Conclusion: The study confirms the Champion Breast Cancer Fear Scale as a valid and reliable measure for identifying women with a fear of breast cancer.